(untitled) (Innovative professional education, 2025)
The article discussed the quality assurance system of vocational education in French-speaking Belgium, focusing on the French Qualifications Framework. It analyzes the implementation of the competence-based approach and certification based on learning outcomes, as well as the role of various institutions in ensuring the quality of education. Based on the Belgian experience, the article highlights the key features of improving the system of quality assurance in vocational education and training and the assessment of competencies acquired in the process.